Small batch bakes - Kimber, Edd (Kyle Books, 2022)
"Baking recipes typically serve large groups, which is perfect for a party, a celebration or a crowd, but not when there's just one or two of you and you would rather not spend the money on making a big batch, or be faced with eating leftovers for a week. Following on from the huge success of One Tin Bakes and One Tin Bakes Easy, Great British Bake Off winner Edd Kimber's new book proves that good things really do come in small packages! It offers accessible, easy bakes that are perfect for singles, small households, students or anyone who likes to bake a lot. Primarily sweet, the recipes include cookies, cakes, tarts and bars a well as desserts and a sprinkling of savoury breads, buns and pies. The skill level is on the easier side, and equipment is kept to a minimum, so everyone can have a little of what they fancy"--Publisher's description